EFFECT OF SWISS BALL EXERCISE TOWARD THE BODY BALANCE TO LESS THE RISK FALL OF OLDER AT UPT SOCIAL - Henny Syapitri (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2016)
Abstract The balance of body is one of the main factor in doing fungsional activity. In every activity, the body always need control of the body balance, because basically every phisic activity right static or dinamic will take someone on unstable position with big risk to having fell. Swiss Ball exercise as support is believed on labile surface will make spine have big chance to stabling the muscle between vebra and increase the dinamic balance to restrain the repeats stability. The research object to know The Effect of Swiss Ball Exercise toward The Body Balance to Less The Risk Fall of Older at UPT Social Service of Older and Children Under Five district Binjai and Medan in Year 2016. The research type is Quasi Experiment with pre test-post test one group only design method. Population in this research all of older at UPT Social Service district Binjai as much as 172 older with number of man is 81 and woman is 91, with Purposive sampling Technique that is 15 respondences. Data collecting using observation sheet with analysis that used is univariat: respondence characteristics, the body balance of older before and after doing Swiss Ball practice, and bivariat with Paired t-Test. The research result showing the average of body balance before doing Swiss Ball as much (Mean 38,07) and after (Mean 46,33). Conclusion: there is the effect of Swiss Ball toward body balance to less the risk fall of older (p=0,000 ; p=< 0,05). Sugessted for older to practice the balance himself more steady so that not easy to have risk fall further. Influenced, and for the next researcher can research about another factor that foregrounded the risk fall of older.Keywords    : Swiss Ball, Balance Exercise, Risk Fall